Assessment of Acute Obstetrical Needs and the Potential Utility of Point-Of-Care Ultrasound in the North East Region of Haiti: A Cross-Sectional Study. Issue 1 (3rd July 2020) - Gomes, Danica J.; Kaufman, Benjamin; Aluisio, Adam R.; Kendall, Scott; Thomas, Vladimir; Bloem, Christina
Background: Point-of-care ultrasound (POCUS) implemented through task shifting to nontraditional users has potential as a diagnostic adjuvant to enhance acute obstetrical care in resource-constrained environments with limited access to physician providers. Objective: This study evaluated acute obstetrical needs and the potential role for POCUS programming in the North East region of Haiti. Methods: Data was collected on all women presenting to the obstetrical departments of two Ministry of Public Health and Population (MSPP)-affiliated public hospitals in the North East region of Haiti: Fort Liberté Hospital and Centre Medicosocial de Ouanaminthe. Data was obtained via retrospective review of hospital records from January 1 through March 31, 2016. Trained personnel gathered data on demographics, obstetrical history, diagnoses, clinical care and outcomes using a standardized tool. Diagnoses a priori, defined as those diagnoses whose detection could be assisted with POCUS, included multi-gestations, non-vertex presentation, cephalopelvic disproportion, placental abruption, placenta previa, spontaneous abortions, retained products and ectopic pregnancy. Results: Data were collected from 589 patients during the study period. Median maternal age was 26 years and median gestational age was 38 weeks. The most common reason for seeking care was pelvic pain (85.2%). Sixty-seven (11.5%) women were transferred to other facilities for higher-level care. Among cases not transferred, post-partum hemorrhage, infant mortality and maternal mortality occurred in 2.4%, 3.0% and 0.6% of cases, respectively. There were 69 cases with diagnoses that could have benefited from POCUS use. Between sites, significantly more cases had the potential for improved diagnostics with POCUS at Fort Liberté Hospital (19.8%) than Centre Medicosocial de Ouanaminthe (8.2%) (p < 0.001). Conclusion: Acute obstetrical care is common and POCUS has the potential to impact the care of obstetrical patients in the North East region of Haiti. Future programs evaluating the feasibility of task shifting and the sustainable impacts of acute obstetric POCUS in Haiti will be important.